Clinical and microbiological patterns in critically ill patients with catheter-associated UTI: A report from Iran - Mohammadreza Salehi; Dariush Robati; SeyedAhmad SeyedAlinaghi; Arash Seifi; Amir Aliramezani; Seyed Ali Dehghan Manshadi; Pegah Afarinesh Khaki; Fariba Zamani (Journal of Infection in Developing Countries)
Introduction: Catheter-associated urinary tract infections (CAUTIs) are among the most common nosocomial infections with different clinical and microbiological characteristics. We studied these characteristics in critically ill patients.